Bilateral Trade Agreements: the Colombian Case (1990-2015) - Rojas Sánchez, Carolina; Gómez Olaya, Álvaro Pío (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The proliferation of bilateral trade agreements has created a phenomenon known in the literature as “hub and spoke” bilateralism. In this context, Colombia’s trade policy is geared towards the signing of bilateral trade agreements. This article evaluates the policy of signing bilateral agreements implemented by Colombia between 1990 and 2015. We analyse trade flows between Colombia and several countries using Baldwin’s HM index of hub-ness (2004) and the matrix of Chen (2008). The results obtainedquestion the Colombian policy of signing trade agreements.